Henry Corbett: A Geriatric Standardized Patient Case - Pamela Basehore; Anita Chopra; Kevin Overbeck (Association of American Medical Colleges, 2013)
Abstract Introduction With the increasing number of geriatric patients filling exam rooms, it is of the utmost importance to train future doctors how to interact with this patient population. To address this, faculty members from the New Jersey Institute for Successful Aging at the University of Medicine and Dentistry of New Jersey's School of Osteopathic Medicine (UMDNJ-SOM) developed a summative standardized patient (SP) case. Successful execution of the SP role requires the SP to study and commit to memory the details of a patient's life and illness complaint. SPs must attend training sessions on a regular basis to ensure validity and reliability in case performance. Methods The Henry Corbett SP case was implemented as one of six stations in a year-end clinical skills comprehensive examination (CSCE) for third-year medical students. Students had to earn an overall passing grade on the exam to progress to their fourth year of training. Performance on the Henry Corbett case was examined using calculated cut scores, which are established for all CSCE cases. Calculated cut scores are configured by subtracting one standard deviation below the mean from the Behavior section (weighted .66) and subtracting one standard deviation below the mean from the ISE section (weighted .33). These two weighted numbers are added together to establish a cut score for the case. Results The case was utilized in both the 2011 and 2012 CSCEs at UMDNJ-SOM. In 2012, 89% of students taking the CSCE (N = 135) scored above the calculated cut score, indicating that they were displaying a high percentage of minimal competency on the Henry Corbett case. Discussion The Henry Corbett SP case is a very effective clinical assessment tool. The circumstances surrounding the case presentation lead to an enriching clinical encounter between a medical student and a geriatric patient. The combination of possible diagnoses and the age of the presenting patient make this SP encounter unique.